Kinematical analysis of the volleyball auction in preyouth and youth players of the pichincha sports concentration - Lasluisa, E. D. G.; Vela Rodríguez, J. M. (Recent advances in biomechanics, 2020)
The finish is an essential element since it is a major action within offensive elements that help the team get points, so it is necessary to analyze each of the phases of this foundation. As such need is to analyze the different angles of movement, speed and center of mass to establish kinematic reference values of the gain shape values that can serve as a reference when the technique of the players so potentiate the driving habit means is analyzed optimizing sports training at all levels. The authors of this study aimed to biomechanically analyze the phases of the auction volleyball in prejuvenile and young players of Pichincha sports concentration. They studied 19 volleyball players from the Pichincha sports concentration under non-probability purposive sampling, with 11 athletes from the prejuvenile team and 8 youth team athletes. Kinovea to measure software (experimental version) was used and the U test was used Mann-Whitney SPSS d e13 digital camera megapixels, measuring tape and HP computer with Intel Core i5 processor. In the approach phase, there was no significant difference in regard to the column angle (p = 0.457). In whipped phase, no significant difference in column angle (p = 0.283). In the preparation phase for beating on the angle of the elbow, there is no significant difference (p = 0.83). In the striking phase at the angle of the elbow if there is significant difference (p = 0.002). In the decay phase in the column angle no significant difference (p = 0.83). This was established with the Mann-Whitney U test. Column angles do not significantly influence the auction technique. However, the influence of angles of the elbow was observed, for better elbow flexion and hand placement can generate a greater impact on the ball and therefore greater difficulty in opposing defense.